Type II ZnO-MoS2 Heterostructure-Based Self-Powered UV-MIR Ultra-Broadband p-n Photodetectors - Badi Zhou; Xiaoyan Peng; Jin Chu; Carlos Malca; Liz Diaz; Andrew F. Zhou; Peter X. Feng (Molecules)
This study presents the fabrication and characterization of ZnO-MoS2 heterostructure-based ultra-broadband photodetectors capable of operating across the ultraviolet (UV) to mid-infrared (MIR) spectral range (365 nm–10 μm). The p-n heterojunction was synthesized via RF magnetron sputtering and spin coating, followed by annealing. Structural and optical analyses confirmed their enhanced light absorption, efficient charge separation, and strong built-in electric field. The photodetectors exhibited light-controlled hysteresis in their I-V characteristics, attributed to charge trapping and interfacial effects, which could enable applications in optical memory and neuromorphic computing. The devices operated self-powered, with a peak responsivity at 940 nm, which increased significantly under an applied bias. The response and recovery times were measured at approximately 100 ms, demonstrating their fast operation. Density functional theory (DFT) simulations confirmed the type II band alignment, with a tunable bandgap that was reduced to 0.20 eV with Mo vacancies, extending the detection range. The ZnO-MoS2 heterostructure’s broad spectral response, fast operation, and defect-engineered bandgap tunability highlight its potential for imaging, environmental monitoring, and IoT sensing. This work provides a cost-effective strategy for developing high-performance, ultra-broadband, flexible photodetectors, paving the way for advancements in optoelectronics and sensing technologies.